2010
DOI: 10.1007/s12640-009-9149-3
|View full text |Cite
|
Sign up to set email alerts
|

Impulsivity as Long-Term Sequelae After Chlorpyrifos Intoxication: Time Course and Individual Differences

Abstract: Chlorpyrifos (CPF) is a common organophosphate (OP) insecticide that has been widely used in agriculture as a pesticide. The primary mechanism of acute toxic action of OPs is initiated by acetylcholinesterase (AChE) inhibition. However, non-AChE targets have also been proposed as alternative that contributes to the acute lethal action and side effects of short or long-term exposure. Recently, we have found that a single dose of 250 mg/kg CPF produces acceleration in acquisition on schedule-induced polydipsia (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
27
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 81 publications
(100 reference statements)
8
27
1
Order By: Relevance
“…In this condition hopelessness may be more associated with suicide than depression [28]. Also we did not find any association between the AChE activity and the impulsivity level of patients, in contrast to studies which reported a relationship between OPs exposure and impulsivity in rats [29]. The variation in impulsivity and depression levels may be caused by OPs exposure dose dependently; this could be established by studies on larger populations.…”
Section: Discussioncontrasting
confidence: 87%
“…In this condition hopelessness may be more associated with suicide than depression [28]. Also we did not find any association between the AChE activity and the impulsivity level of patients, in contrast to studies which reported a relationship between OPs exposure and impulsivity in rats [29]. The variation in impulsivity and depression levels may be caused by OPs exposure dose dependently; this could be established by studies on larger populations.…”
Section: Discussioncontrasting
confidence: 87%
“…As expected according to the literature (Cañadas et al, 2005;Cardona et al, 2006Cardona et al, , 2011López-Granero et al, 2013;Pope et al, 1992;Sánchez-Santed et al, 2004), no signs of acute toxicity were observed after CPF administration (data not shown), except for a reduction of body weight for the doses of CPF 125 and CPF 250 (F (3,44) = 11.33; p < 0.05).…”
Section: Toxicity Evaluationsupporting
confidence: 88%
“…Several studies have reported about the relation between cognitive impairments and short-term OPs intoxication (Bushnell and Moser, 2006;Bushnell et al, 2001;López-Crespo et al, 2007;López-Granero et al, 2013). Moreover, we found long-term effects in memory and impulsive behaviour (Cañadas et al, 2005;Cardona et al, 2006Cardona et al, , 2011Sánchez-Santed et al, 2004) in absence of this toxicity and when the AChE activity is restored (Pope et al, 1992). These previous results seem to point to other mechanism, besides AChE inihibion, could explain these long term squeals.…”
Section: Introductionsupporting
confidence: 75%
See 2 more Smart Citations